Utilization of Waste Shells as Cao Catalyst in Biodiesel Production from Used Cooking Oil - Umei Latifah Azzahro; Wisnu Broto (Acta Chimica Asiana, 2022)
This research is motivated by the depletion of energy reserves while the need continues to grow. Biodiesel is an alternative fuel produced from vegetable oil, animal fat, waste oil, etc. This study aims to determine the best transesterification treatment variables and the most significant main effect using the 2 level 3 factorial design method and operating times of 50 minutes and 70 minutes. The maximum transesterification condition was found by adding a 4% (w/w) CaO catalyst, 70 minutes of transesterification time, and 70 oC of operating temperature. The biodiesel characteristics obtained were a viscosity value of 4.8908 cSt, a density of 853.2 kg/m3, a yield of 78.1%, and a cetane number of 39. The most significant effect was the percentage of catalysts.